A stretchable, electroconductive tissue adhesive for the treatment of neural injury - Jharana Dhal; Mahsa Ghovvati; Avijit Baidya; Ronak Afshari; Curtis L. Cetrulo Jr; Reza Abdi; Nasim Annabi (Bioengineering & Translational Medicine)
Abstract Successful nerve repair using bioadhesive hydrogels demands minimizing tissue–material interfacial mechanical mismatch to reduce immune responses and scar tissue formation. Furthermore, it is crucial to maintain the bioelectrical stimulation‐mediated cell‐signaling mechanism to overcome communication barriers within injured nerve tissues. Therefore, engineering bioadhesives for neural tissue regeneration necessitates the integration of electroconductive properties with tissue‐like biomechanics. In this study, we propose a stretchable bioadhesive based on a custom‐designed chemically modified elastin‐like polypeptides (ELPs) and a choline‐based bioionic liquid (Bio‐IL), providing an electroconductive microenvironment to reconnect damaged nerve tissue. The stretchability akin to native neural tissue was achieved by incorporating hydrophobic ELP pockets, and a robust tissue adhesion was obtained due to multi‐mode tissue–material interactions through covalent and noncovalent bonding at the tissue interface. Adhesion tests revealed adhesive strength ~10 times higher than commercially available tissue adhesive, Evicel®. Furthermore, the engineered hydrogel supported in vitro viability and proliferation of human glial cells. We also evaluated the biodegradability and biocompatibility of the engineered bioadhesive in vivo using a rat subcutaneous implantation model, which demonstrated facile tissue infiltration and minimal immune response. The outlined functionalities empower the engineered elastic and electroconductive adhesive hydrogel to effectively enable sutureless surgical sealing of neural injuries and promote tissue regeneration.